Fenomena Zakat Dan Status Hukum Zakat Di Negara Muslim Dan Beberapa Wilayah Di Indonesia - Nur Azizah (Tasharruf: Journal Economics and Business of Islam, 2019)
Zakat is often seen as a very long problem, an ordinary matter and lacks a future in terms of its development. This is due to the legal status of zakat in Law NO. 23 of 2011 is not something that is required as an Indonesian citizen, but as a form of obedience in worship. Next is the lack of awareness of obligatory zakat people to issue zakat. However, there are actually some things that can overcome these problems. basically the regional government has the authority to establish laws in its territory, there are also several articles in the Zakat Management Act (Law NO 23 of 2011) on the role of regional governments, and some regions in Indonesia are quite successful with some of their applications. In this paper some systems of zakat implementation are reviewed in the regions of Indonesia and other Muslim countries which can be taken into consideration for the progress of zakat in Indonesia.Zakat kerap dipandang sebagai persoalan yang sangat lama, perihal yang biasa dan kurang memiliki masa depan dalam hal pengembangannya. Hal ini disebabkan status hukum zakat dalam UU NO. 23 Tahun 2011 bukanlah sesuatu yang diwajibkan sebagai warganegara Indonesia, tetapi sebagai bentuk ketaatan dalam beribadah. Berikutnya adalah kurangnya kesadaran orang-orang wajib zakat untuk mengeluarkan zakat. Meskipun demikian, sebenarnya ada beberapa hal yang dapat mengatasi problem-problem tersebut. pada dasarnya pemerintah daerah berwenang dalam pembentukan hukum di wilayah kekuasaannya, terdapat juga beberapa pasal dalam UU Pengelolaan Zakat (UU NO 23 Tahun 2011) tentang peran pemerintah daerah, serta beberapa wilayah di Indonesia cukup sukses dengan beberapa penerapannya. Dalam tulisan ini diulas beberapa sistem penerapan zakat di wilayah-wilayah Indonesia dan negara muslim lainnya yang dapat dijadikan pertimbangan untuk kemajuan zakat di Indonesia.